Controlled synthesis of MoₓW₁₋ₓTe₂ atomic layers with emergent quantum states - Deng, Ya (2022)
Recently, new states of matter like superconducting or topological quantum states were found in transition metal dichalcogenides (TMDs) and manifested themselves in a series of exotic physical behaviors. Such phenomena have been demonstrated to exist in a series of transition metal tellurides including MoTe2, WTe2, and alloyed MoxW1–xTe2. However, the behaviors in the alloy system have been rarely addressed due to their difficulty in obtaining atomic layers with controlled composition, albeit the alloy offers a great platform to tune the quantum states. Here, we report a facile CVD method to synthesize the MoxW1–xTe2 with controllable thickness and chemical composition ratios. The atomic structure of a monolayer MoxW1–xTe2 alloy was experimentally confirmed by scanning transmission electron microscopy. Importantly, two different transport behaviors including superconducting and Weyl semimetal states were observed in Mo-rich Mo0.8W0.2Te2 and W-rich Mo0.2W0.8Te2 samples, respectively. Our results show that the electrical properties of MoxW1–xTe2 can be tuned by controlling the chemical composition, demonstrating our controllable CVD growth method is an efficient strategy to manipulate the physical properties of TMDCs. Meanwhile, it provides a perspective on further comprehension and sheds light on the design of devices with topological multicomponent TMDC materials.